PENGARUH SIZE, PROFITABILITAS, LEVERAGE DAN CAPITAL INTENSITY RATIO TERHADAP MANAJEMEN PAJAK - Fitriana , Eti; Isthika, Wikan (Jurnal Riset Akuntansi (JUARA), 2021)
This research aims to find out the effect of size, profitability, leverage, and capital intensity ratio on tax management. This research uses data over the period 2014 to 2018 from manufacturing companies listed in Indonesia Stock Exchange. Whereas, as the samples are consumer goods sectors companies. The determination of sample was made by applying purposive sampling methods. Multiple linear regression technique was used to analyze the data. Furthermore, from the testing data, this research shows that size and capital intensity ratio have an effect on the tax management. Whereas, profitability and leverage have no effect on the tax management.